Lessons on Outbreak Preparedness From the Cleveland Clinic - Orsini, Erica (Chest, 2020)
Disasters, including infectious disease outbreaks, are inevitable. Hospitals need to plan in advance to ensure that their systems can adapt to a rapidly changing environment if necessary. This review provides an overview of 10 general principles that hospitals and health-care systems should consider when developing disaster plans. The principles are consistent with an “all-hazards” approach to disaster mitigation. This approach is adapted to planning for a multiplicity of threats but emphasizes highly relevant scenarios, such as the coronavirus disease 2019 pandemic. We also describe specific ways these principles helped prepare our hospital for this pandemic. Key points include acting quickly, identifying and engaging key stakeholders early, providing accurate information, prioritizing employee safety and mental health, promoting a fully integrated clinical response, developing surge plans, preparing for ethical dilemmas, and having a cogent exit strategy for post-disaster recovery.